Chronic kidney disease as a predictive factor for poor prognosis in traumatic brain injury among older adults: a case-control study - Mo, Haoyang; Fan, Fan; Liu, Jian; Zhang, Wenfan; Wang, Qing; Yuan, Xiangning (Frontiers in Neurology, 2023)
Objective: Traumatic brain injury (TBI) is a highly prevalent neurological disorder that affects a gradually increasing proportion of older adults. Chronic kidney disease (CKD) significantly contributes to global years of life lost, with an estimated one-tenth of the global population affected by CKD. However, it remains unclear whether CKD impacts TBI prognosis. We conducted a case-control study to investigate the clinical outcomes of TBI patients with or without CKD comorbidity and identified the risk factors associated with a poor prognosis. Methods: From January 2017 through April 2023, 11 patients with TBI and CKD were included, and 27 control TBI cases with normal kidney function were matched by age, gender, and admission Glasgow Coma Scale (GCS) score as the control group. Results: The CKD TBI group had a significantly lower GCS score upon discharge (7.1±5.9) compared to the non-CKD TBI group (13.1±2.6) (p<0.01). ICU stay time and hospitalization expenses were higher in the CKD group than the non-CKD group, though there were no statistical differences. Additionally, patients in the CKD TBI group had a higher frequency of hospital-acquired infections (54.4%) compared with those in the non-CKD TBI group (7.4%) (p<0.01). The two groups exhibited no differences in hemoglobin levels, albumin levels, or coagulation function. Logistic regression analysis showed that advanced age, low admission GCS score, elevated blood urea, and creatinine levels were associated with a poor neurological prognosis. Conclusion: TBI patients comorbid with CKD have a poorer prognosis than those with normal kidney function.